Translating empire: Tell Fekheriyeh, deuteronomy, and the Akkadian treaty tradition - Crouch, Carly L. (Forschungen zum Alten Testament, 2019)
Cover -- Titel -- Preface -- Contents -- Abbreviations -- 1. Introduction -- 1.1. Translating Empire -- 1.2. Discovery and Historical Context of the Tell Fekheriyeh Inscription -- 1.3. The Object and Its Inscription -- 1.3.1. The Text of the Inscription(s) -- 1.3.2. The Physical History of the Statue and Its Inscription -- 1.3.3. "Double-Bilingualism" or Multiple Moments of Translation? -- 1.4. Prospectus -- 2. "Optimal Translation": A Theoretical Précis -- 2.1. Optimality Derives from Norms -- 2.2. Descriptive Translation Studies and Optimality Theory: A Comparison -- 2.2.1. Range of Possible Alternatives -- 2.2.2. Assumption of Optimality (~ Equivalence) -- 2.2.3. Assumption of Universal Constraints -- 2.2.4. Limited and Hierarchical Constraint Sets -- 2.2.5. Universal vs. Language- and Culture-Specific Constraints -- 2.3. Optimality Theoretic Constraints on Translation -- 3. Building the Optimal Grammar of Translation in Fekheriyeh A -- 3.1. High-Level Norms: Pairwise Comparison of IDENTITY Constraints -- 3.1.1. TRPROPNS &gt -- &gt -- CHLINGSYS -- 3.1.2. IDENT:SEM &gt -- &gt -- IDENT:LEX -- 3.1.3. IDENT:PRAG.LEX &gt -- &gt -- IDENT:SEM -- 3.1.4. Summary -- 3.2. Mid- and Low-Level Norms: Comparison of MAX, DEP, and LINEAR Constraints -- 3.2.1. EXPLIC-COORD &gt -- &gt -- DEP:MORPH -- 3.2.2. FAVOR-NWS_CONV &gt -- &gt -- MAX:MORPH -- 3.2.3. EXPLIC-PRO &gt -- &gt -- DEP:MORPH -- 3.2.4. EXPLIC-QUANT &gt -- &gt -- DEP:MORPH -- 3.2.5. DEIXISCONS &gt -- &gt -- IDENT:MORPH -- 3.2.6. SYNCONS, NWS-SYN &gt -- &gt -- LINEAR:LEX -- 3.2.7. Summary -- 3.3. Comparison of Multiple Constraints -- 3.3.1. FAVOR-LOC.TTL &gt -- &gt -- IDENT:SEM -- 3.3.2. *NEWLOAN &gt -- &gt -- IDENT:SEM -- 3.3.3. Difficult Assessments and the Use of Multiple Constraints to Evaluate Longer Strings -- 3.3.4. Optimality Theory, Translation, and Philological Reasoning -- 3.3.5. Summary.